Mortality risk conferred by small elevations of creatine kinase-MB isoenzyme after percutaneous coronary intervention - Ioannidis, John P.A; Karvouni, Evangelia; Katritsis, Demosthenes G (Journal of the American College of Cardiology, 2003)
The aim of this study was to assess whether small creatine kinase-MB isoenzyme (CK-MB) elevations after percutaneous coronary intervention (PCI) affect the subsequent mortality risk. Several studies have evaluated the relationship of CK-MB levels after PCI with the subsequent risk of death. While there is consensus that elevations exceeding 5 times the upper limit of normal increase mortality significantly, there is uncertainty about the exact clinical impact of smaller CK-MB elevations. We performed a meta-analysis of seven studies with CK-MB measurements and survival outcomes on 23,230 subjects who underwent PCI. Data were combined with random effects models. Mean follow-up was 6 to 34 months per study. By random effects, 19% (95% confidence interval [CI], 16% to 23%) had one- to five-fold CK-MB elevations, while only 6% (95% CI, 5% to 9%) had >5-fold elevations. Compared with subjects with normal CK-MB, there was a dose-response relationship with relative risks for death being 1.5 (95% CI, 1.2 to 1.8, no between-study heterogeneity) with one- to three-fold CK-MB elevations, 1.8 (95% CI, 1.4 to 2.4, no between-study heterogeneity) with three- to five-fold CK-MB elevations, and 3.1 (95% CI, 2.3 to 4.2, borderline between-study heterogeneity) with over five-fold CK-MB elevations (p < 0.001 for all). Any increase in CK-MB after PCI is associated with a small, but statistically and clinically significant, increase in the subsequent risk of death.